Evaluation and surgical outcome of inverted nipple at Kathmandu Medical College Teaching Hospital - Bajracharya, Amir (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Inverted nipples are related to multifactorial aspects, relating with aesthetic, biological, and psychological to the patient. The treatment depends on the patient’s symptoms and aesthetic complaints caused by the inverted nipple. The objective of this study was to evaluate the grading of inverted nipple and the surgical outcome by using Sakai method for its correction. Methods: It is a hospital based descriptive study conducted to assess age, sex, site, shape, grading. The history of peri-areolar abscess, recurrence and treatment outcome by Sakai method for its correction. Results: A total of 20 patients were included with 26 cases of inverted nipple in which six cases of bilateral, nine cases of left sided and five cases of right sided. The mean age was 30±8.399 years ranging from 18 to 52 years. Most of them were females 19(95%). We found grade II inverted nipple on 16(80%) of patients and grade III inverted nipple on 4(20%). Most of them were round shape 16(50%), rest were rectangular 4(20%), slanting 3(15%), omega 2(10%) and one with cup shape nipple. Patients were followed up for three months for observation. Conclusions: The common type of inverted nipple was Grade II followed by Grade III and the defects were successfully corrected using Sakai method.